In-vitro Anti-Diabetic activity of leaves of Cicer arietinum - Mhamane, Supriya (Indian Journal of Pharmacy & Drug Studies, 2024)
Chickpea, (Cicer arietinum), also known as garbanzo bean or Bengal gram, yearly plant of the pea family Fabaceae, widely grown for its beneficial seeds. Chickpeas are cultivated in more than 50 countries. Largest areas under chickpeas are India, Pakistan, Ethiopia, Turkey and Mexico. This study incorporates the Cicer arietinum leaves anti diabetic activity. It has traditional medicinal uses like anti-diabetic and it is also used in illness to optimize the taste. This work envisaged the anti-diabetic activity of leaves of Cicer arietinum by using UV-Visible spectrophotometer at 540nm. The maximum peak of inhibition of alpha-amylase is observed at 10μg/ml.